AND AGAIN MEDUSA RHZOSTOMA PULMO IN THE SEA OF AZOV - Парталы, Елена; Бутенко, Алексей (SWorldJournal, 2021)
According to the observations of over 50 years, in 2020 jellyfish Rhizostoma pulmo appeared in the Taganrog Bay and in the Mariupol region after being absent in 45 years